Anti-Gastric Cancer Effect of Purified Omphalia lapidescens Protein via Regulating the JAK/STAT3 Signaling Pathway. (28th May 2022) - Xu, Yuqin; Xu, Wenjun; Lu, Zhongxia; Cheung, Man Hei; Lin, Meiai; Liang, Chun; Lou, Jianshu; Chen, Yitao
Abstract: Gastric cancer is the leading cause of cancer-related death worldwide. The aim of present study was to investigate the anti-tumor effect of purified Omphalia lapidescens protein (pPe O p) in gastric cancer. Microarray analysis was performed to find out differentially expressed genes in pPe O p-treated MC-4 gastric cancer cells. The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) three signaling pathway was most likely to be altered based on bioinformatics analysis. Interleukin-6 (IL-6) and NSC74859 were used as the agonist and inhibitor of the JAK/STAT3 signaling pathway, respectively. Flow cytometry and MTS assay were used for cell proliferation and viability analysis in pPe O p-treated gastric cancer cell lines with IL-6 or NSC74859. The anti-tumor effect was increased when pPe O p were co-treated with IL-6, while decreased in inhibitor treatment. The expression of the crucial members in the pathway of MC-4 cells, including glycoprotein 130 (GP130), JAK1, JAK2, STAT3, p-STAT3, suppressor of cytokine signaling SOCS1 and SOCS3, was detected by western blotting. pPe O p exhibited promising anticancer effect in the xenograft nude mice model, established by STAT3 knock down gastric cancer cells.Thus, JAK/STAT3 inhibition partially contributed to the anticancer effect of pPe O p, which may serve as a novel strategy for gastric cancer. Supplemental data for this article is available online at https://doi.org/10.1080/01635581.2021.1960385